Stoichiometric and non-stoichiometric tungsten doping effect in bismuth vanadate based photoactive material for photoelectrochemical water splitting. (10th March 2019) - Prasad, Umesh; Prakash, Jyoti; Azeredo, Bruno; Kannan, Arunachala
Abstract: In photoelectrochemical (PEC) water splitting, BiVO4 has attracted attention due to its favorable band gap but it suffers low PEC performance due to poor conductivity. The vast majority of publications on this system has examined doping of stoichiometric composition of tungsten (W) on this system to increase bulk and interfacial conductivity while managing the contaminant generation of crystallographic defects and recombination sites. In this paper, a deep investigation was carried out to examine the effect of non-stoichiometric W doping in BiVO4 system. Stoichiometric and non-stoichiometric W-doped monoclinic BiVO4 (i.e. Bi1-(x+δ) V1-x Wx+δ O4 ; BiV1-x Wx+δ O4 and BiV1-y Wy O4; x = 0.008; y = 0.03 and δ = 0.005) were prepared using a facile dip coating technique. The stoichiometric composition contains charge balanced Bi, V and W atoms whereas non-stoichiometric compositions contain excess Bi and excess Bi and W. The non-stoichiometric composition BiV1-x Wx+δ O4 has shown better photoelectrochemical water splitting performance with respect to other compositions at 1.23 V vs RHE, under one sun illumination of electrode. The XRD and XPS results shows that non-stoichiometric doping with excess Bi or with excess Bi and W can possibly create an environment where V 5+ ions are substitutional replaced by W 6+ ions without generating other defects. But there was no significant difference in band gap of different compositional samples observed. Further electrochemical impedance technique was used to analyze change in bulk and surface charge mobility with W-doping in BiVO4 . The electrochemical impedance analysis showed the presence of low interfacial resistance, lower charge transfer resistance and high charge donor/surface state density for non-stoichiometric composition BiV1-x Wx+δ O4 electrode. It is evident from and cyclic voltammetry that the addition of excess Bi and W from its stoichiometric quantity efficiently suppressed the formation of hole-electron pair recombination sites. The electrochemical analytical results lead us to believe that the particular non-stoichiometric composition of BiV1-x Wx+δ O4 can significantly lower trap sites and enhances kinetics of charge transfer, leading to the better photoelectrochemical water splitting performance. Graphical abstract: Image 1 Highlights: Excess Bi and W doping in BiVO4 lead to favorable bulk and surface properties. BiV0.992 W0.013 O4 showed low interfacial resistance and higher charge density. BiV0.992 W0.013 O4 exhibited maximum PCD of 2.27 mA cm −2 at 1.23 V vs NHE.